Reception of the Qur'an on Social Media: Case Study of Qur'an Interpretation on the Instagram Account @quranreview - Ach Fadoli; Sakinah Naziha; Wasik (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Qur’an is a guide and holy book for Muslims whose presence is accepted. The current study of Qur’an studies places reception as one that is often discussed. This research is based on the idea of Ahmad Rafiq's reception. Then this study analyzes the reception of the Qur'an on social media. This study aims to describe the reception on the Instagram account @quranreview, which actively uploads interpretations of verses of the Qur’an. Because receptions are the result of human thought, and of course, the results will vary, the author feels the need to raise this discussion to add to the body of knowledge related to the practice of the Qur'an. The research method is a virtual ethnographic qualitative method, which collects data from online information instead of interviews and surveys. The primary data sources are posts from the @quranreview account supported by secondary data sources such as scientific journals. After the data is collected, it is analyzed with the stages of reduction, display, and data verification. The results found in the study are that there are three receptions of the Qur'an in the @quranreview account, including the reception of exegesis, aesthetic reception, and functional reception. The reception that is most prominent and dominating in this account is the reception of exegesis because it is an account that focuses on studying the interpretation of the Qur'an. Other receptions, such as aesthetic and functional, are also found through postings of verse interpretations.